Monetary policy transmission in segmented markets - Jens Eisenschmidt; Yiming Ma; Anthony Lee Zhang (European Central Bank (ECB), 2022)
We show that dealer market power impedes the pass-through of monetary policy in repo markets, which is an important first stage of monetary policy transmission. In the European repo market, most participants do not have access to trade on centralized exchanges. Rather, they rely on OTC intermediation by a small number of dealers that exhibit significant market power. As a result, the passthrough of the ECB's policy rate to the majority of non-dealer banks and non-banks is inefficient and unequal in repo markets. Our estimates imply that a secured funding facility like the Fed's RRP may alleviate dealer market power and improve the transmission efficiency of monetary policy to banks and non-bank financial institutions.
Keywords: E4; E5; G2; 330; monetary policy; pass-through efficiency; non-banks; repo market; market power